EFEKTIVITAS PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) DI PT. PLN (PERUSAHAAN LISTRIK NEGARA) ULPLTD (UNIT LAYANAN PEMBANGKIT LISTRIK DIESEL) KOLAKA - Akramila, Nurul; Malik, Ihyani; Umar, M Amin (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThis study aims to determine the effectiveness of the implementation of the Corporate Social Responsibility (CSR) Program at PT. PLN (Persero) ULPLTD Kolaka. The type of research used is a qualitative research method with a descriptive type of research. The results of the study are 1) Achieving Goals, it is enough to see the maximum targets and goals achieved, which are apart from being the responsibility of the company as well as for the welfare of the community. 2) Integration, it is not maximized, seeing that the company does not really socialize and communicate with the community evenly but focuses more on socialization and communication to the local government, so that the community does not really understand the Corporate Social Responsibility (CSR) program. 3) Adaptation, has been maximal enough considering that several Corporate Social Responsibility (CSR) programs that have been carried out are in accordance with the needs of the target or community. Keywords: Corporate Social Responsibility, Effectiveness